Effects of nitrogen management on grain yield and nitrogen use efficiency of two hybrid rice varieties with different panicle masses - Yang Shimin; Yang Zhiyuan; Sun Yongjian; Ma Jun (浙江大学学报. 农业与生命科学版)
In Sichuan Basin with low solar radiation, the grain yield of hybrid rice was restricted by the high humidity and small diurnal temperature. The breeding and application of large panicle hybrid varieties solved the problem to a certain extent. However, the high-yielding performance of large panicle hybrid rice was not stable.In order to explore the measures of maintaining the high-yielding performance of large panicle hybrid rice, it is necessary to investigate the characters of its grain yield formation. Two hybrid varieties with different panicle masses (Chuannongyou 498, about 5 g per panicle; Chuanyou 6203, about 4 g per panicle) were studied on the differences of dry matter accumulation and yield components, and five different nitrogen (N) managements (the N application proportion of base-tillering and panicle fertilizers was 90∶10, 75∶25, 60∶40, 45∶55, 30∶70, respectively) integrated with 15N tracing were applied to investigate the traits of N uptake across the whole growth stage.The results showed that there was no significant difference in spikelet per panicle between large and medium panicle hybrid rice. Medium panicle hybrid rice showed significant advantages in effective panicles and total spikelet compared to large panicle hybrid rice; however, the thousand-grain mass of large panicle hybrid rice was larger, and this superiority played a major role in gaining higher grain yield than medium panicle hybrid rice. There was no significant difference in dry matter accumulation at maturity stage between large and medium panicle hybrid rice, but difference of dry matter productivity was observed before and after anthesis. Compared to medium panicle hybrid rice, large panicle hybrid rice accumulated more dry matters before anthesis, and larger percentage of which was exported to the panicle at anthesis, contributing approximately 40% of its grain yield. For medium panicle hybrid rice, dry matter exportation only contributed about 25% of its grain yield. For N management treatments, 40% and 25% were the optimal panicle N ratios which could gain the highest grain yields for large and medium panicle hybrid rice respectively. According to the relation formula between panicle N ratio and grain yield, 33% was the optimal panicle N ratio which produced the most grains for large panicle hybrid rice, while the optimal panicle N ratio for medium panicle hybrid rice was 27%. The difference for the optimal panicle N ratio between large and medium panicle hybrid rice was caused by varied demands on N at different growth stages. There was no significant difference for N uptake of basal fertilizer between large and medium panicle hybrid rice. Medium panicle hybrid rice showed significant merits in assimilating N at tillering stage than large panicle hybrid rice. In contrast, large panicle hybrid rice assimilated more N at booting stage. A further increase of panicle N based on the optimal panicle N ratio could increase N recovery efficiency, but N physiological efficiency would drop rapidly and the yield-increasing effects of N fertilizer became poor.In conclusion, 33% and 27% are the optimal panicle N ratios for large and medium panicle hybrid rice, respectively, which increase the grain yield and N utilization efficiency simultaneously.